2016
DOI: 10.1115/1.4033887
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Calculate Leak Channels and Leak Rates Between Metallic Sealing Surfaces

Abstract: Surface topography of sealing interface is a key factor affecting sealing performance. In industry, it has always been desirable to optimize the performance of static seals by optimizing the surface topography. The evolution of leak channels and the quantitative effects of surface topography on leak rates are expected to be clarified. This paper proposes a novel approach to calculate leak channels and leak rates between sealing surfaces for specific surface topographies, based on three-dimensional (3D) finite-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…Statistical analysis using a general linear test approach (Neter et al, 1996) demonstrated that the diffusion term in the leakage model was negligible compared to the pressure term. This is in line with the approaches used by Bottiglione et al (2009; and Zhang et al (2017). As directly shown by Fick's law of diffusion, the rate at which a gas diffuses is proportional to the area of the surface over which the diffusion process takes place and the concentration gradient.…”
Section: Leakage Is a Pressure Driven Processsupporting
confidence: 89%
See 1 more Smart Citation
“…Statistical analysis using a general linear test approach (Neter et al, 1996) demonstrated that the diffusion term in the leakage model was negligible compared to the pressure term. This is in line with the approaches used by Bottiglione et al (2009; and Zhang et al (2017). As directly shown by Fick's law of diffusion, the rate at which a gas diffuses is proportional to the area of the surface over which the diffusion process takes place and the concentration gradient.…”
Section: Leakage Is a Pressure Driven Processsupporting
confidence: 89%
“…This might result in small percolation channels allowing gas flow between the cool room and environment (Bottiglione et al, 2009(Bottiglione et al, ,2016Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The comments we make are, however, general to all domains of both topographies studied. Moreover, the shape of the curve presented in Figure 5 has been observed in many theoretical observations [16,[28][29][30][31] as well as experimental studies [1,32], considering both elastic and elasto-plastic materials.…”
Section: Qualitative Descriptionsupporting
confidence: 64%
“…On the contact area, it needs the contact analysis to judge the contact width required, to ensure the sealing performance of the contact area. Based on the commonly used leakage model A Roth, this project has improved, the cone contour surface is simplified as a plane and the globe surface is simplified as a cylinder [4][5], whose radius is the radius of the globe. The improved model is shown in figure 7.…”
Section: Contact Area Criterionmentioning
confidence: 99%